Upaya Peningkatan Kemampuan Berpikir Kritis Siswa Melalui Model Inquiry Di Kelas V - Gustriyono Gustriyono (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research aims to describe out the improvement of students' critical thinking skills with the application of inquiry model in V grade of primary school. The method used in this research is Classroom Action Research and research design used is Kemmis and McTaggart model which begins with planning, implementation and observation, and reflection. The subjects involved 40 students of Srengseng Sawah State Elementary School. Collection data techniques used were interviews, observations, and tests. The results showed that the achievement obtained at the time of pretest implementation is 15%, after the implementation of the first cycle is completed students' critical thinking achievement increased 40% to 55%. This research shows that the application of guided inquiry model can improve students' critical thinking ability in primary school.